Assessment of Landslide Susceptibility by Decision Trees in the Metropolitan Area of Istanbul, Turkey. (17th February 2010) - Nefeslioglu, H. A.; Sezer, E.; Gokceoglu, C.; Bozkir, A. S.; Duman, T. Y.
Abstract : The main purpose of the present study is to investigate the possible application of decision tree in landslide susceptibility assessment. The study area having a surface area of 174.8 km 2 locates at the northern coast of the Sea of Marmara and western part of Istanbul metropolitan area. When applying data mining and extracting decision tree, geological formations, altitude, slope, plan curvature, profile curvature, heat load and stream power index parameters are taken into consideration as landslide conditioning factors. Using the predicted values, the landslide susceptibility map of the study area is produced. The AUC value of the produced landslide susceptibility map has been obtained as 89.6%. According to the results of the AUC evaluation, the produced map has exhibited a good enough performance.